2012
DOI: 10.1007/s13205-012-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and antioxidative enzymes defence mechanism on occurrence of yellow vein mosaic disease of pumpkin (Cucurbita moschata)

Abstract: Pumpkin (Cucurbita moschata) samples showing yellow vein mosaic disease in Varanasi region were identified with begomovirus infection using PCR amplification. A sequencing analysis of the full genome revealed that it is a strain of Tomato leaf curl Palampur virus (GenBank ID. FJ931537). Phytochemical composition and antioxidative enzyme levels were compared in infected and healthy plants. The study revealed that the amount of total protein declined in the infected leaves but elevated up to 135 % in the fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
(46 reference statements)
3
19
0
Order By: Relevance
“…A modified method of Jaiswal et al (2013) was used for isoenzyme profiling of SOD. Native PAGE was carried out by 10% polyacrylamide gels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified method of Jaiswal et al (2013) was used for isoenzyme profiling of SOD. Native PAGE was carried out by 10% polyacrylamide gels.…”
Section: Methodsmentioning
confidence: 99%
“…The imbalances found between ROS production and its scavenging by antioxidative enzymes in leaves may reflect defense strategy shown by plants or develop into pathogen success. Defense enzymes such as SOD, CAT, GR, glutathione- S -transferase (GST), APx, guaiacol peroxidase (GPx), and peroxidases (POx), as well as some non-enzymatic antioxidants such as glutathione (GSH), tocopherols, carotenoids, ascorbate, flavonoids, proline, and other phenolic compounds ( Gill and Tuteja, 2010 ; Sharma et al, 2012 ; Kapoor et al, 2015 ) as it was reported that the activities of defense-related enzymes found to increase several folds during environmental stresses ( Jaiswal et al, 2013 ). CAT, play an important role in detoxifying the activated oxygen species ( Sharma et al, 2012 ) and breakdown peroxide molecules to oxygen and water ( Das and Roychoudhury, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These phytochemicals include secondary metabolites viz. carotenoids, alkaloids, flavonoids, terpenoids [12]. The secondary metabolites have polyhydroxy group which is responsible for their strong antioxidant activity and free radical scavenging property, and may also play a major role in the reduction of metal ions into nanoparticles [13].…”
Section: Introductionmentioning
confidence: 99%
“…Only one isozyme in our study may be due to a high turnover rate in plant organ and a much lower affinity with H 2 O 2 compared with APX and GPX [81]. Another reason probably is that moderate temperature regime reduced expression of CAT isozymes [82]. Meanwhile, three forms of GPX isozymes were separated in all three treatment ( Figure 5C).…”
Section: Physiological Responses Of Seedlings Under Various Temperatumentioning
confidence: 67%
“…Our data imply that multiple isozymes of APX come into play in this process. For example, Jaiswal et al [82] showed a different expression of APX isozymes between healthy and infected pumpkin leaves by native PAGE. Ahn et al [83] found a diverse expression of APX isozymes among cultivars of apple.…”
Section: Physiological Responses Of Seedlings Under Various Temperatumentioning
confidence: 99%